Development and control of caries lesions on the occlusal surface using a new in vivo caries model (Pesquisa Odontológica Brasileira, 2003)
The aim of this study was to develop a new in vivo caries model for the occlusal surface and to describe the enamel features observed before and after dental plaque control (DPC). Four volunteers (12-15 years old) participated in the experiment, each of which was due to have 2 homologous first premolars extracted for orthodontic reasons. Test surfaces did not present visible signs of demineralization, opacities or fillings. A wire mesh was used to promote dental plaque accumulation on the occlusal surface. After 4 weeks, the wire mesh was removed and DPC was performed. In Groups 1 and 2, DPC was performed by the subjects daily and, in Groups 3 and 4, DPC was performed by the subjects daily and by the professional weekly. One tooth/pair of Groups 1 and 3 was extracted after 2 weeks. One tooth/pair of Groups 2 and 4 was extracted after 4 weeks. All test surfaces showed demineralization after the wire mesh was removed. The observed re-establishment of the enamel brightness was directly related to the increase of the DPC duration. In polarized light microscopy, interindividual differences varying from pseudoisotropic areas to enamel lesions were noted in specimens submitted to 2 weeks of DPC. Specimens submitted to 4 weeks of DPC showed less tissue porosity. It was concluded that the new in vivo caries model was effective since all occlusal surfaces presented clinical and microscopic signs of mineral loss in different stages after 4 weeks of cariogenic challenge. After DPC on the test surfaces, there was a reduction of mineral loss suggesting control of demineralization on these surfaces.